Flexural behaviours of semi-precast lightweight foam concrete beam - Muhammad Amirul Asyraf, Adanan (2014)
Lightweight foam concrete is revolution of concrete from conventional concrete due to density. The major materials that contains in lightweight foam concrete are cement, water, fine sand and foam. -This study focus on the reduce weight of lightweight foam. With reduce a weight of beam, the contractor can using manpower to lift up the beam and the contractor can save money from rent or used lift machinery on site. The aim in this study was to investigate the performance of semi-precast Lightweight Foam Concrete beam in term of flexural strength, deflected shape and failure mode. Lightweight foam concrete in study was used sand cement ratio (sic) and water cement ratio (w/c) which is 1.5 and 0.5 respectively. The width and length of the beam was constant which are 150mm and 3000mm respectively. Four samples with different height which is 200mm, 180mm, 170mm and 160mm were designated as Beam 1, Beam 2, Beam 3 and Beam 4 respectively. All samples were painted and tested under four point test. Linear Variable Displacement Transducers (LVDT) was connected to data logger to determine the flexural strength and deflected shape. Four point tests also can be determining the ultimate load of concrete that it can stand before failure. Based on the result from those outcomes which can obtain- are the deflection measurements of the beam also the crack pattern by the observations. The result shows that the flexural strength of the samples was increase to certain degree of percentage of 27.430% and 34.311% which is Beam 3 and Beam 4. For deflection result shows that Beam 2. Beam 3 and Beam 4 was comparing to Beam 1 and the percentage of increment 1%, 134.263% and 40% respectively. All the beams show the same deflection profile. The first crack loading for Beam 1, Beam 2, Beam 3 and Beam 4 was 8.72kN, 8.59kN, 6.95kN and 5.94kN respectively. The crack pattern result shows the behaviour.